Cybercrime Legislation in Lesotho - Maliehe, Mamotumi (Department of Commercial Law, 2014)
This paper advocates introducing cybercrime legislation in Lesotho. Cybercrime is the hottest issue today. Cybercriminals can commit various illegal activities in cyberspace that few people even know exist. A nightmare scenario would be a hacker breaking into the hospital's computer systems on a fine morning and before doctors can arrive to treat their patients, the malicious hacker modifies patients' files on the hospital's database systems: [S]urgeries slated to be performed on the right leg are now switched to the left leg; recorded blood types are altered from AB-negative to O-positive; warnings for known allergies to medicines such as penicillin are electronically erased from patients' charts; and laboratory records on HIV blood tests results are insidiously switched from negative to positive just before patients are to receive their results. (Marc D Goodman 'Why the police don't care about computer crime' (1997) 10 Harvard Journal of Law and Technology 465 at 466). Although this scenario is possible with current technology, unfortunately Lesotho would be powerless to act for lack of adequate laws to investigate and prosecute this conduct. Lesotho's current criminal laws can hardly be enforced against cybercrime, as they do not clearly prohibit the crime. Therefore, this paper argues that Lesotho must adopt a comprehensive legal structure to deter and prosecute cybercrime. It does this by examining international and national approaches to cybercrime, with a view to providing guidance for an effective framework capable of addressing this 'new' crime. Cybercrime is a major global challenge requiring coordinated international effort. In a networked world no island is an island; cybercrime penetrates all countries because of its ability to cross national boundaries. Further, this paper suggests a model law that is based on the first international treaty which plays a key role in combating cybercrime. Finally, it recognises that legislation alone cannot fight cybercrime; law enforcement must be equipped to implement the law, and private citizens must know about cybercrime and the need to protect themselves and their systems and networks.